2017
DOI: 10.1089/met.2017.0042
|View full text |Cite
|
Sign up to set email alerts
|

Low-Volume High-Intensity Interval Training Is Sufficient to Ameliorate the Severity of Metabolic Syndrome

Abstract: Low-volume HIIT (51 min/week) was as effective as high-volume HIIT (114 min/week) and MICT (150 min/week) in ameliorating MetS severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
55
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 26 publications
11
55
2
Order By: Relevance
“…It has also been proven that both exercise modalities could be recommended for T2Dpatients. This finding is consistent with the result obtained by Ramos et al, who found that low-volume HIIT could be as effective as moderate-intensity continuous training in reduction of the MetS Z-score (32).…”
Section: Discussionsupporting
confidence: 93%
“…It has also been proven that both exercise modalities could be recommended for T2Dpatients. This finding is consistent with the result obtained by Ramos et al, who found that low-volume HIIT could be as effective as moderate-intensity continuous training in reduction of the MetS Z-score (32).…”
Section: Discussionsupporting
confidence: 93%
“…There are currently few interventional studies that we are aware of that have examined metabolic syndrome z-score responses to exercise interventions in individuals with T2D. Nonetheless, the decreased risk observed in the current study appears superior to a recent study examining z-score risk in individuals with T2D undergoing 16 weeks of either moderate-intensity continuous training 5 days per week (41% reduction), or HIIT 3 days per week (51% or 1% protocol-dependent reduction) (Ramos et al, 2017). This may be due to the fact that the participants started with higher average baseline z-score values.…”
Section: Discussioncontrasting
confidence: 70%
“…It has also been proven that both exercise modalities could be recommended for type2 diabetes patients. This finding is consistent with the results obtained by Ramos et al, who found that low-volume HIIT could be as effective as moderate-intensity continuous training in the reduction of the MetS Z-score [ 51]. In addition, Fisher and colleague demonstrated that both high intensity interval training and continuous moderate intensity training are associated with improvements in cardiovascular risk factors (body fat percent, cholesterol, VLDL, HDL, triglycerides and VO2peak) in overweight men [ 52].…”
Section: Discussionsupporting
confidence: 90%